MODEL PELATIHAN PENANGGULANGAN BENCANA DALAM MENINGKATKAN KEMANDIRIAN MASYARAKAT (Studi Di Daerah Rawan Longsor Kawasan Cadas Pangeran Kabupaten Sumedang Propinsi Jawa Barat) - Sutaryat Trisnamansyah; Nurjanah Nurjanah (Sosio Konsepsia, 2010)
This research aims to develop a training model of disaster management which is backgrounded by problems of disaster management in Indonesia. The problems are factually still slowgoingly patially an top-downly handed by the government. Recenly, the existing management is still emergency respond oriented and handled by inadequate human resources as well. As a matter of fact, the occurrences of disaster in Indonesia have to be aware of disaster preparedness anytime. Empowering theon; in disaster preparedness,study of adult (andragogy)and a theon; concerning training become the main references of this research. This research is conducted by using R & D method (Research &Development Method). Data collection technique was supported by circumstantial interviews, questioners, observation and documentation. Data analysis technique was applied for the Path Analysis. The research location of critical landslide areas is a long Cadas Pangeran main road, the country side of Ciherang District of South Sumedang as a group experimental and the country side of Cigendel, District of Pamulihan in Kabupaten Sumedmzg as a group control. In conclusion, disaster management training model trhough locality empowennent is factually effective to be implemented to improve society self-reliance in landslide natural disaster management. This models has significantly effected the improvement of knowledge, awareness and attitude of the society living around vulnerable landslide areas in the disaster management at before, at time and after the disaster has occurred. Critical factors wich influence the success of Non Formal Educaion to improve society self-reliance in landslide disaster management are; (1) Society competence in disaster management before disaster occurred pre disaster,(2) Society competence in disaster management at the time disaster occures and (3) Societty competence in disaster management after disaster has occurred. The proposed recommendations are as to the local govenzment and practitioners of disaster management , they are supposed to be able to implement the disaster management training model through locality empowerment by following phases which have been eximained to the people living in the vulnerable landslide areas.